Acne and risk of mental disorders: A two-sample Mendelian randomization study based on large genome-wide association data - Liu, Lin; Xue, Yuzhou; Chen, Yangmei; Chen, Tingqiao; Zhong, Judan; Shao, Xinyi; Chen, Jin (Frontiers in Public Health, 2023)
Background Despite a growing body of evidence that acne impacts mental disorders, the actual causality has not been established for the possible presence of recall bias and confounders in observational studies. Methods We performed a two-sample Mendelian randomization (MR) analysis to evaluate the effect of acne on the risk of six common mental disorders, i.e., depression, anxiety, schizophrenia, obsessive–compulsive disorder (OCD), bipolar disorder, and post-traumatic stress disorder (PTSD). We acquired genetic instruments for assessing acne from the largest genome-wide association study (GWAS) of acne (N = 615,396) and collected summary statistics from the largest available GWAS for depression (N = 500,199), anxiety (N = 17,310), schizophrenia (N = 130,644), OCD (N = 9,725), bipolar disorder (N = 413,466), and PTSD (N = 174,659). Next, we performed the two-sample MR analysis using four methods: inverse-variance weighted method, MR-Egger, weighted median, and MR pleiotropy residual sum and outliers. Sensitivity analysis was also performed for heterogeneity and pleiotropy tests. Results There was no evidence of a causal impact of acne on the risk of depression [odds ratio (OR): 1.002, p = 0.874], anxiety (OR: 0.961, p = 0.49), OCD (OR: 0.979, p = 0.741), bipolar disorder (OR: 0.972, p = 0.261), and PTSD (OR: 1.054, p = 0.069). Moreover, a mild protective effect of acne against schizophrenia was observed (OR: 0.944; p = 0.033). Conclusion The increased prevalence of mental disorders observed in patients with acne in clinical practice was caused by modifiable factors, and was not a direct outcome of acne. Therefore, strategies targeting the elimination of potential factors and minimization of the occurrence of adverse mental events in acne should be implemented.